Look who's talking: An analysis of actors in television news (2003–2016). (26th April 2019) - Beckers, Kathleen; Van Aelst, Peter
Abstract : Who gets to speak in the news plays a crucial role in the shaping of the news. Consequently, the study of actors in the news is an enduring topic in journalism studies. However, little systematic knowledge exists about differences between news issues in the occurrence of speaking actors. Based on a new fourfold classification of actors in the news, we study differences in actor prevalence over time, between broadcasters and issues. To do so, we analyze the entire population of television news items in Belgium from the two main broadcasters for the period 2003 to 2016. While we do not find large changes over time, significant differences exist between issues in the actors that get to speak in the news. Moreover, the prevalence of speaking actors differs between the public service and commercial broadcaster, even when controlling for news issues.